Thermo-hydro-mechanical behaviour of cold reclaimed asphalt aggregates without binder addition. (30th April 2019) - Gaillard, Laura; Chazallon, Cyrille; Hornych, Pierre; Quezada, Juan Carlos; Raab, Christiane
Abstract : This paper details a cold recycling evaluation of 100% reclaimed asphalt aggregates without any binder addition. In this context, a series of triaxial laboratory tests was performed. Monotonic triaxial tests were conducted to determine failure resistance at 20°C, 50°C and with a specimen preheated at 50°C then tested at 20°C. Repeated Load Triaxial (RLT) tests were performed to analyse the permanent and resilient strains at 20°C, at three frequencies and with two water contents. It is found that increasing temperature causes a drop of failure resistance while cohesion is increased. RLT tests reveal that higher water content implies higher strains, as well that water content presents a higher impact on resilient behaviour than low frequencies. Finally, the non-linear elastic Boyce model was used to describe the resilient strains. Total stress and effective stress calibrations were performed with a measurement of the initial suction. Eventually, these effective stress calibrations were performed with one set of parameters.